IMF Glossary : English-French-Arabic, Third edition. (International Monetary Fund, 2008)
The main body of the Glossary consists of terms, phraseological units, and institutional titles covering areas such as macroeconomics, money and banking, public finance, taxation, balance of payments, statistics, accounting, and economic development.